Ecology of melanoma cell - Lacina, Lukáš; Kodet, Ondřej; Dvořánková, Barbora; Szabo, Pavol; Smetana, Karel (Histology and histopathology, 2018)
Melanoma represents a cancer with increasing incidence worldwide and limited curability of advanced stages of the disease. Similarly to other types of tumors, the microenvironment is an important factor that participates in the control of melanoma biological properties. This review summarizes data regarding the role of the microenvironment, namely fibroblasts, keratinocytes and infiltrating immune cells, on melanoma growth and spreading. The role of embryonic microenvironment on melanoma cell biological properties is also discussed. The potential of therapeutic targeting of the melanoma microenvironment is demonstrated.
Keywords: nádorové mikroprostředí; Melanoma; lidé; Tumor Microenvironment; melanom; Humans